Cultural Diversity and Mental Health: Considerations for Policy and Practice - Gopalkrishnan, Narayan (Frontiers in Public Health, 2018)
The purpose of this paper is to explore some of the key considerations that lie at the intersection of cultural diversity and mental health. Mental health providers and professionals across the world have to work with clients that are often from cultures other than their own. The differences in cultures have a range of implications for mental health practice, ranging from the ways that people view health and illness, to treatment seeking patterns, the nature of the therapeutic relationship and issues of racism and discrimination. This paper will excavate some of these considerations with a view to raising possible ways in which mental health systems and professionals can engage across cultures more equitably and sustainably.